A Geothermal-Solar Hybrid Power Plant with Thermal Energy Storage - Brady Bokelman (Energies, 2020)
The concept of a geothermal-solar power plant is proposed that provides dispatchable power to the local electricity grid. The power plant generates significantly more power in the late afternoon and early evening hours of the summer, when air-conditioning use is high and peak power is demanded. The unit operates in two modes: a) as a binary geothermal power plant utilizing a subcritical Organic Rankine Cycle; and b) as a hybrid geothermal-solar power plant utilizing a supercritical cycle with solar-supplied superheat. Thermal storage allows for continuous power generation in the early evening hours. The switch to the second mode and the addition of solar energy into the cycle increases the electric power generated by a large factor—2 to 9 times—during peak power demand at a higher efficiency (16.8%). The constant supply of geothermal brine and heat storage in molten salts enables this power plant to produce dispatchable power in its two modes of operation with an exergetic efficiency higher than 30%.